Contratación pública ecuatoriana en el acuerdo comercial con la Unión Europea (Tema Central) - Aguirre Ribadeneira, Juan Fernando (2016)
This paper deals with Ecuador´s accession to the Multiparty Trade Agreement (MTA) with the European Union (EU) and its effects on the National Public Procurement System due to the opening of markets. It has been more than two years since July 2014 that the Negotiating Committee of Ecuador signed a preliminary agreement. No internal actions have been taken to inform about the content of the agreement and its scope, neither system operators have been trained (suppliers, institutions, structures responsible for public procurement, supportive bodies, supervision bodies). In Ecuador in 2008 the Organic Law of the National System of Public Procurement –LOSNCP– was issued, encouraging the national component of the products purchased and especially supporting the participation of the grassroots solidarity economy and micro, small and medium-sized units. In response to the agreement, what changes should be made to the conditions of participation of suppliers? Is the present constitutional and legal system of preferences appropriate? We will approach this issue through the review and legal analysis of this international agreement on public procurement, pointing out challenges and opportunities.